2021
DOI: 10.3390/life11060501
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinography and Gene Expression Measures Implicate Phototransduction and Metabolic Shifts in Chick Myopia and Hyperopia Models

Abstract: The Retinal Ion-Driven Fluid Efflux (RIDE) model theorizes that phototransduction-driven changes in trans-retinal ion and fluid transport underlie the development of myopia (short-sightedness). In support of this model, previous functional studies have identified the attenuation of outer retinal contributions to the global flash electroretinogram (gfERG) following weeks of myopia induction in chicks, while discovery-driven transcriptome studies have identified changes to the expression of ATP-driven ion transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 78 publications
(130 reference statements)
3
9
0
Order By: Relevance
“…The gfERG findings in human in human myopes reviewed here build on electrophysiological, structural, and pharmacological evidence from animal models implicating the photoreceptors and ON- and OFF- bipolar cell pathways in the control of eye growth and the development of myopia [ 18 , 19 , 20 , 57 ]. The human studies reviewed here consistently concur with the findings of gfERG studies in chick models of early and established myopia identifying decreased a-wave and b-wave amplitudes [ 36 , 37 , 38 , 39 ]. Using a quantitative model of phototransduction, Westbrook et al [ 39 ] derived the photoreceptor light response in myopic and emmetropic chick eyes from the leading edge of the a-wave.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The gfERG findings in human in human myopes reviewed here build on electrophysiological, structural, and pharmacological evidence from animal models implicating the photoreceptors and ON- and OFF- bipolar cell pathways in the control of eye growth and the development of myopia [ 18 , 19 , 20 , 57 ]. The human studies reviewed here consistently concur with the findings of gfERG studies in chick models of early and established myopia identifying decreased a-wave and b-wave amplitudes [ 36 , 37 , 38 , 39 ]. Using a quantitative model of phototransduction, Westbrook et al [ 39 ] derived the photoreceptor light response in myopic and emmetropic chick eyes from the leading edge of the a-wave.…”
Section: Discussionsupporting
confidence: 81%
“…The function of each cell type can be inferred by measuring the size of each wave (amplitude) and the difference in time between onset of the response and maximum response reached (implicit time). Consistent with the animal model pharmacological research outlined above, attenuation of the gfERG a-wave and b-wave amplitude has been demonstrated in studies of optically and pharmacologically induced myopia in chicks [ 36 , 37 , 38 , 39 ]. However, although gfERG has been used extensively in clinical settings to examine human myopia e.g., [ 40 , 41 , 42 , 43 , 44 ]; the findings have been mixed, and current knowledge has not been systematically reviewed.…”
Section: Introductionsupporting
confidence: 58%
“…In this study, we revealed a shift toward OXPHOS in highly myopic photoreceptors. Similar metabolic alternations in myopic eyes have also been also mentioned in previous studies, which used bulk RNA sequencing of retinas 6,32 …”
Section: Discussionsupporting
confidence: 79%
“…reported that “abnormal photoreceptor inner segment morphology” was the most significant gene set enriched for myopia‐associated genes; other photoreceptor‐related gene sets include the “thin retinal outer nuclear layer”, “detection of light stimulus”, and “nonmotile primary cilium” 2 . Previous functional studies have also confirmed the attenuation of photoreceptor cell responses to flash electroretinography (a‐wave and d‐wave) in a murine model of myopia 6 . However, the underlying molecular mechanism was largely unknown.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation